Pediatric Non-Myofibroblastic Primitive Spindle Cell Tumors with ALK Gene Rearrangements and Response to Crizotinib. (September 2022) - Rakheja, Dinesh; Park, Jason Y.; Fernandes, Neil J.; Watt, Tanya C.; Laetsch, Theodore W.; Collins, Rebecca R. J.
We describe two poorly differentiated, non-myofibroblastic (SMA−, S100+, CD34±), spindle cell neoplasms with immunohistochemical positivity for ALK and with ALK gene rearrangements leading to PLEKHH2::ALK and CLTC::ALK fusions, respectively. ALK protein overexpression and/or gene fusions should be evaluated in poorly differentiated spindle cell neoplasms, even when there is an absence of a myofibroblastic phenotype. A positive ALK evaluation has therapeutic implications as both tumors responded to single-agent treatment with the tyrosine kinase inhibitor crizotinib.